Factors Influencing Quality of Life among Patients with Type 2 Diabetes Mellitus (T2DM) at Waled General Hospital, Cirebon, Indonesia - Hidayat, Abimanyu; Zein, Ahmad Fariz Malvi Zamzam; Suwarno, Hermansyah (GHMJ (Global Health Management Journal), 2025)
Background: Diabetes Mellitus (DM) is a chronic disease that requires long-term management and carries the risk of leading to other health conditions, which can result in decrease of quality of life. Aims: To find the quality of life of patients with Type 2 Diabetes Mellitus (T2DM) and the factors affecting it at Waled General Hospital (RSUD Waled), Cirebon, Indonesia. Methods: It was an analytic observational study with a cross-sectional approach. The study took place at RSUD Waled, Cirebon Regency, and used 96 (T2DM) patients as research samples that were chosen with simple random sampling. The source of data was primary through a questionnaire and secondary from the patient’s medical record. The questionnaire used for the quality of life’s variable in this research was WHOQOL-BREF. The analytical statistics used were Spearman’s correlation test for the bivariate analytics, and binary logistics regression for the multivariate analytic. Results: There were 54.2% of T2DM patients that fell into bad quality of life category and 45.8% of T2DM patients had good quality of life. Analytic statistics showed a significant relationship between glycemic control (p = 0.003 and r = 0.304), family support (p = 0.000 and r = 0.502), and self-acceptance with quality of life of T2DM patients (p = 0.000 and r = 0.606). Meanwhile types of therapy, comorbidities, and complication didn’t show a significant correlation with quality of life of T2DM patients. Multivariate analysis showed the most correlated factor for quality of life of patients T2DM was self-acceptance (OR=30). Conclusion: There were some factors that had significant correlation with quality of life of T2DM patients. Self-acceptance was the most correlated factor with quality of life of T2DM patients. Healthcare providers can incorporate educational intervention programs into routine diabetes care, emphasizing patients' psychological health, especially with regard to self-acceptance and family support techniques. In order to improve knowledge, motivation, and efficient self-management, this program may incorporate counselling, education, and the creation of support groups.